(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article clarifies the concept of pedagogical conditions and proposes pedagogical conditions for activating students’ extracurricular educational activities using digital technologies.